Urgensi Pendidikan Karakter Aswaja Dalam Upaya Membangun Softskill Mahasiswa - Azizi, Faizah (An Nahdhoh Jurnal Kajian Islam Aswaja, 2023)
Character education is very important for humans from the level of education, starting from formal and non-formal education, because from character education a person can do good things easily, can consider positive and negative things in society. Of course students are obliged to study character education, students as agents of change for the intellectual elite group who must be able to get involved in preparing themselves for society. Aswaja Nahdlatul Ulama as jam'iyyah diniyyah Islamiyyah who has faith/based on Islam understands Ahlussunnah Wal-Jama'ah has values ​​that must be implemented so that the behavior reflects Aswaja's character in facing society and the challenges of the future. In the movement on campus institutes or universities, students can hone their hard skills and soft skills. Not only in the formal campus learning space but also in campus organizations or organizations under the auspices of the Nahdlatul Ulama. NU students absolutely apply NU values, the pillars of Hubbul wathon are a firm grip on always being enthusiastic about continuing the struggle for Hadratus sheikh KH. Hasyim Asy'ari and the Muasis and Indonesian Heroes. Starting from here, an appropriate and innovative Aswaja NU character education strategy is urgently needed.